Microsurgical Techniques Used to Construct the Vascularized and Neurotized Tissue Engineered Bone. (12th May 2014) - Fan, Junjun; Bi, Long; Jin, Dan; Wei, Kuanhai; Chen, Bin; Zhang, Zhiyong; Pei, Guoxian
Abstract : The lack of vascularization in the tissue engineered bone results in poor survival and ossification. Tissue engineered bone can be wrapped in the soft tissue flaps which are rich in blood supply to complete the vascularization in vivo by microsurgical technique, and the surface of the bone graft can be invaded with new vascular network. The intrinsic vascularization can be induced via a blood vessel or an arteriovenous loop located centrally in the bone graft by microsurgical technique. The peripheral nerve especially peptidergic nerve has effect on the bone regeneration. The peptidergic nerve can be used to construct the neurotized tissue engineered bone by implanting the nerve fiber into the center of bone graft. Thus, constructing a highly vascularized and neurotized tissue engineered bone according with the theory of biomimetics has become a useful method for repairing the large bone defect. Many researchers have used the microsurgical techniques to enhance the vascularization and neurotization of tissue engineered bone and to get a better osteogenesis effect. This review aims to summarize the microsurgical techniques mostly used to construct the vascularized and neurotized tissue engineered bone.